Teacher’s Belief of Motivational Strategies Implemented in ABC Course Sidoarjo - Anettia Raharjo (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
A motivational strategy is seen as an important factor in learning language. This study was conducted to find out teacher’s beliefconcerning motivational strategiesand motivational strategies used by the teacher in the Basic 1 class of ABCcourse. The theory applied in this study was motivational strategies by Dörnyei (2001). This study used qualitative approach. The data were the answers from the teacher’s interview and questionnaire and also teacher’s utterances and gestures in the classroom related to motivational strategies. In order to collect the data of the study, the writer used three instruments: interview, questionnaire, and classroom observation. The writer found out that the teacher believed in all motivational strategies. However there were were two strategies that were not used in the classrom namely goals and related values.The writer found out some motivational strategy elements that have perfect 6 ratio in the questionnaire, yet it was not used so much often in the classroom such as Relevant Materials and Task. In conclusion, the teacher implemented motivational strategies in the classroom in order to engage the students in the learning process.